Why does underperformance of IPOs in the long-run become debatable? A theoretical review - Perera, W.; Kulendran, N. (International Journal of Accounting & Business Finance, 2016)
Attached

Prior studies have examined initial public offering (IPO) market performance in two different periods-short run and long run-in terms of two phenomena: the underpricing or short-run market phenomenon and the underperformance or long-run market phenomenon. Tofind out the possible theoretical reasons for the underperformance phenomenon, this study reviews the past literature on the long-run market performance ofIPOs. The evidence on long-run underperformance of IPOs is not as widespread as that of short-run underpricing ofIPOs. The previous researchers have explained long-run performance using behavioural theories, methodological issues and short-run underpricing theories. Some researchers have found that IPOs underperform marginally or have no abnormal performance in the long run; thus, they do not reject the market efficiency hypothesis in the long run. Others have reported that IPOs overperform or do not underperform in the longrun market. Still others have argued that underperformance disappears when different performance measures or methodologies are used. The rest have found that' IPOs underperform considerably in the long-run IPO market. However, the long-run underperformance ofIPOs is a debatable issue amongfinancial researchers because of their studies Iconflicting results and controversial findings.
Keywords: Behavioural theories; Efficiency Market hypothesis; IPO; Under performance